PELAYANAN YANG MEMBAWA SHALOM BAGI WARGA BINAAN LAPAS PEREMPUAN KEROBOKAN BALI - Yanti, Yanti; Lindawati, Lindawati (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
Christians are called to carry out the Great Commission in the form of guiding people in the knowledge of Christ. We are called to do mission services that aim to preach love and become a support system for fellow believers, especially in this program is the prisoners of Kerobokan Women's Prison Bali. This is in line with the purpose of the Correctional Institution's mission, which is to provide guidance to community members based on the values of Pancasila to produce law-abiding citizens who are not involved in any form of crime. In reality, many prisons still experience the problem of lack of spiritual guidance agents for their prisoners, one of which is in Kerobokan Bali Correctional Facility. In this regard, the purpose of this mentoring program is to bring shalom to God's people for the female prisoners of Kerobokan Prison by providing spiritual guidance agents for prisoners. This mentoring service is carried out together with the partner foundation BPM (Blessing Prison Ministry). The method of implementation carried out is to provide online and direct (face-to-face) mentoring in prison. The results of this activity are considered to have a positive impact on prisoners, namely providing new goals and hopes in accordance with aspects of rehabilitation. Furthermore, prisoners are also helped to learn to leave the old life and start a new, better life.